Worst-case analysis of maximal dual feasible functions - Rietz, Jurgen Endre (2012)
Dual feasible functions have been used to compute fast lower bounds and valid inequalities for integer linear problems. In this paper, we analyze the worst-case performance of the lower bounds provided by some of the best functions proposed in the literature. We describe some worst-case examples for these functions, and we report on new results concerning the best parameter choice for one of these functions.